FAKTOR-FAKTOR YANG DIPERTIMBANGKAN KONSUMEN DALAM MENGGUNAKAN JASA DELIVERY GO-FOOD PADA APLIKASI GO-JEK DI KABUPATEN BADUNG: Studi Pada Konsumen Go-Food di Kabupaten Badung - Bali - I Wayan Tisyadana; Luh Komang Candra Dewi (Universitas Triatma Mulya, 2020)
This study aims to determine what factors and which factors are the most dominant that consumers consider in using the Go-Food delivery service in the Go-Jek application in Badung Regency. The design of this study used quantitative descriptive analysis with SPSS version 24 analysis tool. This study used 100 respondents as the research sample drawn based on the purposive sampling method. The research method applied in this study is based on analysis of factor analysis with data collection techniques used are interviews, documentation, questionnaires. The results of this study show that only 15 independent variables can be analyzed further from a total of 20 independent variables. Of the 15 variables after the factor rotation process, there are five main components. The naming of new factors is determined according to the variables that make up the factor. The first factor is the service quality and application factors that have the highest eigenvalue value of 5.664 and are able to explain the total variance of 37.759%. The second factor is the individual factor with an eigenvalue value of 2.504 with a variance percentage of 16.692%. The third is the price factor with an eigenvalue value of 2.262 with a total variance of 15.083%. The fourth faculty is a social factor that has an eigenvalue of 1.359 with a total variance of 9.062%. The fifth factor is the lifestyle factor with an eigenvalue value of 1.091 which is able to explain the total variance of 7.273%. Implications for companies to always maintain service quality and also the quality of their applications, as well as to evaluate price, social and lifestyle factors that have small eigenvalue values compared to individual factors and service quality.Keywords: purchasing decisions, consumer behavior.